Cognitive bias and stock investment decisions among the individual investors - Mohan Prasad Sapkota; Shiva Bhandari (Journal of Business and Social Sciences, 2022)
Decision-making is a complex activity and cannot be made in a vacuum. Human behavior is the fundamental concern for stock investment decisions of the individual investors. This study sought to establish the cognitive biases which influence the individual investors’ stock investment decisions. Descriptive cum causal-comparative research design was employed. A sample of 385 individual investors was used among the stock investors in Chitwan district. Final usable responses were collected from 273 individual investors via 5-point Likert-type self-administered closed-end structured questionnaires. Data were analyzed through descriptive and inferential statistics by using SPSS - 25 and MS excel. This study found that overconfidence bias, excessive optimism, herding bias, and accounting information has significant positive influence on equity investment decisions of the investors. Evidence indicates that cognitive bias plays the significant role for stock investment decisions of the investors. Finally, this study concluded that investors should properly aware and handle such biases for better investment decisions to obtained the appropriate return on investment decisions and such biases should be properly handled by the investors through participation in training, education, seminar and information analysis. The study also suggests that the NEPSE and SEBON should offer proper investment education, financial literacy related to stock market and knowledge to investors in order to minimize the adverse effects of such biases.